Development of Flipbook E-Modules of Science for Basic School Students - Hasanah, Qoriatul; Sari, Eka Yuliana (research, training and philanthropy institution Natural Aceh, 2024)
This study aims to develop an e-module flipbook as a learning media that directs active students in using technology in the learning process. The research method used is R&D (Research and Development) with the ADDIE development model (Analysis, Design, development, Implementation, and Evaluation). Data collection is carried out by the steps in the development research process from the data that the researcher has obtained, followed by the process of analyzing the research results that have been obtained. The results showed that the E-module Flipbook Science Style Material was said to be valid and able to encourage students' independent learning interest in learning activities, it can be seen from the media expert scoring 95%